The Effectiveness of Using a Social Story Intervention to Improve Social Interaction Skills of Students with Autism - Al zyoudi, Mohammed; Al Murhairi, Oshua; Sartaiwi, AbedAlziz; Olimat, Enas; Al zyoudi, Abedsalm (Journal of the American Academy of Special Education Professionals, 2016)
The aim of this study was to evaluate the effectiveness of using a social story intervention to improve social interaction skills in three students with autism aged between 7-8 years. A multiple-baseline-across participants design was used. To achieve the purpose of the study, the social stories were implemented. The intervention included reading the social story to the students, and answering questions based on what was read. The results of this study showed an increase in social interaction for all participants. The results suggest that the use of social story-only intervention without additional social skills interventions may be effective in increasing social interaction skills and the frequency of these skills.